Cissus extracts in dentistry: A comprehensive review on its untapped potential - Rohan Shinkre; Edlyn Rodrigues; Ishan Mukherji; Divya Pandya; Rashmi Naik; Anwesha Banerjee (Journal of Pharmacy and Bioallied Sciences, 2024)
Natural products have received a lot of attention in a variety of medical sectors, including dentistry. Cissus, a flowering plant genus, has long been used for its therapeutic benefits. The purpose of this review is to thoroughly investigate the possibilities of Cissus extracts in dentistry. To that end, we used specific selection criteria for the selection of pertinent scientific articles published in the scientific information databases of PubMed, Web of Science, Google Scholar, Scopus, and ProQuest. We found that the diverse array of bioactive compounds found in varied species of Cissus holds promise for applications ranging from oral wound healing to periodontal health. This review summarizes known studies on antibacterial, anti-inflammatory, and tissue-regenerative characteristics of Cissus extracts, shedding light on their potential significance in modernizing modern dental practices. It exerts that Cissus extracts have the potential to supplement established dentistry therapies by providing all-natural remedies for a variety of oral health conditions.